Existence, uniqueness and averaging principle for fractional Dirichlet boundary value problems driven by Rosenblatt process and Lévy jumps - Arokiyanathan, Jalisraj; Udhayakumar, Ramalingam (Nonlinear Analysis: Modelling and Control, 2026)
We address the existence, uniqueness, and averaging principle for Caputo–Hadamard fractional dynamic systems with Dirichlet boundary conditions driven by Rosenblatt process and pure Lévy jumps. First, Lemma 4 establishes the equivalent integral equation representation of our system. Using this foundation, existence and uniqueness are proved by Banach's contraction principle under stochastic calculus, Lipschitz and finite energy conditions. Subsequently, under appropriate averaging assumptions, the system is averaged out with time scale ϵ. Mean-square convergence between original solution and its counterpart is verified by employing tools such as Wiener–Itô double integral, Cauchy–Schwarz, Doob's martingale, and Gronwall–Bellman inequalities. Eventually, computational example with numerical simulations is provided to support the theoretical results.
Keywords: Caputo–Hadamard derivative; stochastic differential equation; averaging principle; Lévy jumps; Rosenblatt process